ACCESSIBLE INTERFACES FOR PEOPLE WITH AUTISM SPECTRUM DISORDER (ASD): an analysis of guidelines - França, Matheus Eduardo; Gambogi, Antonio Sinval Agostinho; Gibertoni, Daniela (Revista Interface Tecnológica, 2022)
Children with autism tend to be less interested in general subjects and sometimes more interested in specific ones. Thinking about technology and interfaces aimed at the autistic public as a way to improve and develop their skills, this work surveyed good practices in the development of interfaces with accessibility and aimed at people with ASD. These guidelines aim to maintain the focus, motivation and interest of autistic individuals when interacting with the application. Thus, through a systematic mapping, four categories were created by skills that provide satisfactory guidelines for creating interfaces for this audience.